2021
DOI: 10.3390/biomedicines9050475
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Disease in Pregnancy and Lactation: A Narrative Review of the Literature

Abstract: Pregnancy and lactation are characterized by sophisticated adaptations of calcium homeostasis, aiming to meet fetal, neonatal, and maternal calcium requirements. Pregnancy is primarily characterized by an enhancement of intestinal calcium absorption, whereas during lactation additional calcium is obtained through resorption from the maternal skeleton, a process which leads to bone loss but is reversible following weaning. These maternal adaptations during pregnancy and lactation may influence or confound the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…In neighbouring Nigeria, the third-trimester prevalence of vitamin D deficiency and insufficiency of 22.5% and 60%, respectively, have been reported [ 38 ]. The prevalence of hypoparathyroidism in the general population is low, ranging from 0.5–6.6% [ 39 ], while the prevalence in pregnancy has not been reported [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In neighbouring Nigeria, the third-trimester prevalence of vitamin D deficiency and insufficiency of 22.5% and 60%, respectively, have been reported [ 38 ]. The prevalence of hypoparathyroidism in the general population is low, ranging from 0.5–6.6% [ 39 ], while the prevalence in pregnancy has not been reported [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inappropriate continuation may lead to hypercalcemia in the mother (and suppression of the fetal parathyroid glands). Tsourdi et al [ 84 ] recommended monitoring calcium every four to six weeks during lactation to ensure that normocalcemia is present and to wean as appropriate. Khan et al [ 83 ] recommended weekly albumin-corrected (or ionized) calcium levels during the first month postpartum, with a target of achieving calcium within the low-normal reference range (in a manner similar to a non-breastfeeding female).…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, records during prior pregnancies should be obtained in women with hypoparathyroidism to assess when hypercalcemia (or hypocalcemia) occurred during a previous pregnancy (or postpartum period) and to consider a proactive dosage reduction in supplementation should hypercalcemia have occurred in a prior pregnancy. As a final consideration, in patients who do require active vitamin D supplementation during gestation and lactation, Tsourdi et al [ 84 ] suggested calcitriol due to its shorter half-life (more rapid recovery from hypercalcemia).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women with hypercalcemia and reduced PTH concentrations may suffer from a variety of diseases including, e.g., disorders of vitamin D metabolism, vitamin D intoxication per se, malignancy, granulomatous diseases (sarcoidosis and tuberculosis), pseudohyperparathyroidism (due to elevated PTH related peptide (PTHrP) levels), milk-alkali syndrome (due to excess intake of calcium and antacid drugs), etc. posing a diagnostic and therapeutic challenge [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%